Host Responses to Malassezia spp. in the Mammalian Skin - Sparber, Florian; LeibundGut-Landmann, Salomé (Frontiers in Immunology, 2017)
The skin of mammalian organisms is home for a myriad of microbes. Many of these commensals are thought to have beneficial effects on the host by critically contributing to immune homeostasis. Consequently, dysbiosis can have detrimental effects for the host that may manifest with inflammatory diseases at the barrier tissue. Besides bacteria, fungi make an important contribution to the microbiota and among these, the yeast Malassezia widely dominates in most areas of the skin in healthy individuals. There is accumulating evidence that Malassezia spp. are involved in a variety of skin disorders in humans ranging from non- or mildly inflammatory conditions such as dandruff and pityriasis versicolor to more severe inflammatory skin diseases like seborrheic eczema and atopic dermatitis. In addition, Malassezia is strongly linked to the development of dermatitis and otitis externa in dogs. However, the association of Malassezia spp. with such diseases remains poorly characterized. Until now, studies on the fungus–host interaction remain sparse and they are mostly limited to experiments with isolated host cells in vitro. They suggest a multifaceted crosstalk of Malassezia spp. with the skin by direct activation of the host via conserved pattern recognition receptors and indirectly via the release of fungus-derived metabolites that can modulate the function of hematopoietic and/or non-hematopoietic cells in the barrier tissue. In this review, we discuss our current understanding of the host response to Malassezia spp. in the mammalian skin.